The EARN-Health Trial: protocol for a randomised controlled trial to identify health effects of a financial savings programme among low-income US adults. Issue 10 (6th October 2015) - Basu, Sanjay; Hamad, Rita; White, Justin S; Modrek, Sepideh; Rehkopf, David H; Cullen, Mark R
Abstract : Introduction: A theory within the social epidemiology field is that financial stress related to having inadequate financial savings may contribute to psychological stress, poor mental health and poor health-related behaviours among low-income US adults. Our objective is to test whether an intervention that encourages financial savings among low-income US adults improves health behaviours and mental health. Methods and analysis: A parallel group two-arm controlled superiority trial will be performed in which 700 participants will be randomised to the intervention or a wait list. The intervention arm will be provided an online Individual Development Account (IDA) for 6 months, during which participants receive a 5 incentive (£3.2, €4.5) for every month they save 20 in their account (£12.8, €18), and an additional 5 if they save 20 for two consecutive months. Both groups will be provided links to standard online financial counselling materials. Online surveys in months 0 (prior to randomisation), 6 and 12 (6 months postintervention) will assess self-reported health behaviours and mental health among participants in both arms. The surveys items were tested previously in the US Centers for Disease Control and Prevention national health interviews and related health studies, including self-reported overall health, health-related quality of life, alcohol and tobacco use, depression symptoms, financial stress, optimism and locus of control, and spending and savings behaviours. Trial data will be analysed on an intent-to-treat basis. Ethics and dissemination: This protocol was approved by the Institutional Review Board of Stanford University (Protocol ID: 30641). The findings of the trial will be disseminated through peer-reviewed publication. Trial registration number: Identifier NCT02185612 ; Pre-results.